Bipolar remitted patients show emotion related bias in memories for lifelike events: Evidence from study based on the virtual reality paradigm. - Bobrowicz-Campos, Elzbieta Malgorzata; Pinho, Maria Salomé; Matos, Ana Paula (Revista de Psicopatología y Psicología Clínica, 2016)
Abstract: This study aimed to examine whether patients with bipolar disorder (BD) perceive differences in the encoding and retrieving of autobiographical information related to events with different emotional valence. For this purpose, an experimental task based on the virtual reality paradigm was administrated to 14 euthymic BD patients and 23 healthy controls. All participants also had a neuropsychological assessment and completed selfreport questionnaires as to mood and psychopathological symptoms. BD patients, when compared to adult controls, recognized more information associated with negative lifelike events and retrieved less information related to positive events. We suggest that changes in processing negative information are caused by the activation of maladaptive emotionregulation processes, and changes in processing positive information arise from insufficient elaboration of memory traces or from suppression/distortion processes acting during retrieval. Resumen: Los pacientes con trastorno bipolar presentan sesgo emocional en memorias de eventos simuladores de la realidad: Estudio basado en el paradigma de realidad virtual. Nuestro objetivo era verificar si los pacientes con trastorno bipolar experimentan alteraciones en la codificación y recuperación de la información autobiográfica, referente a eventos con diferentes valencias emocionales. Una tarea experimental basada en el paradigma de realidad virtual fue administrada a 14 pacientes bipolares eutímicos y 23 adultos sanos. Los partici pantes también fueron objeto de evaluación neuropsicológica y completaron los cuestionarios de autoinforme relativos al estado de ánimo y síntomas psicopatológicos. Los pacientes bipolares, en comparación con los adultos sanos, reconocieron más infor mación asociada a eventos negativos y recuperaron menos información referente a eventos positivos. Se sugiere que las alteraciones en el procesamiento de la información negativa son causadas por la activación de los procesos de regulación emocional desadaptativos, y que las alteraciones en el procesamiento de la información positiva surgen de la elaboración insuficiente de rasgos mnésicos o de procesos de supresión/distorsión que actúan durante la recuperación.